A review of 3D-printed sensors. Issue 7 (9th August 2017) - Ni, Yujie; Ji, Ru; Long, Kaiwen; Bu, Ting; Chen, Kejian; Zhuang, Songlin
ABSTRACT: Nowadays, sensors play an important role in human life. Among the many manufacturing methods used in the fabrication of sensors, three-dimensional (3D) printing has gradually shown its advantages, particularly with commercial products. Physical sensors, biosensors, and chemical sensors can all be fabricated via 3D printing technology, through either directly printing sensing components, printing molds for casting sensors, or printing platforms to be integrated with commercial sensors. In this article, the varieties of features and applications of 3D printing technologies used in the fabrication of sensors are reviewed. Several types of 3D printing technologies are compared for better understanding of the tools. With the development of new or hybrid manufacturing methods and materials used in the 3D printing technology, this technology will show its great advantages and potential in the fabrication of highly sensitive nanosensors or compound sensors with 3D intricate structures.